DEVELOPMENT AND RESEARCH OF THE MODIFIED WHITE METAL MATERIAL WITH THE PURPOSE OF ITS USE AT REPAIR OF HEAVY-LOADED BEARINGS OF SLIPPING - A. V. Alifanov (Литьë и металлургия, 2012)
The paper shows that wear resistance of new modified babbit material (MBM) is by an order of magnitude higher than that of the Б83 State Standard 1320-74 standard babbit material. Therefore, the latter can be recommended for restoration of sliding bearings that are used in gascompressor units.